The War in Ukraine as a Critical Juncture:China, Russia, and the Arctic Collaboration up to 2035 - Kauppila, Liisa; Kopra, Sanna (2022)
The outbreak of the war in Ukraine in February 2022 marks a major watershed in Arctic politics. Declining West- Russia relations have transformative implications for the region’s stability, practices of governance, and economic policies, including a potentially rapid green transition. Moreover, China’s ‘neutrality’ in the West-Russia axis adds on to the high level of uncertainty about the future of the Arctic. Unsurprisingly, this dynamic has sparked a newfound interest in mapping the region’s futures in an analytical and rigorous manner, and, consequently, spawned a growing pool of scenario analyses. Unlike most of these exercises, this article abandons the business-asusual style of reasoning that guides the envisioning of predominantly alarming futures. Instead, it uses the futures research technique of backcasting to construct three scenarios on the continuation of the Arctic cooperation with Sino-Russian relations as the focus. More specifically, the article produces a set of alternative futures that – despite the differences in their actual content and ethos – all picture an Arctic of 2035 where at least the eight Arctic states collaborate regularly, and in which climate change mitigation and adaptation constitutes a key driver of collaboration. With this research strategy, the article seeks to contribute to the efforts to alleviate regional tensions by immersing the readers into a future world of possibilities and hope – despite our deep condemnation of Russia’s war in Ukraine.